2007
DOI: 10.1111/j.1558-5646.2007.00220.x
|View full text |Cite
|
Sign up to set email alerts
|

The Accumulation of Reproductive Barriers During Speciation: Postmating Barriers in Two Behaviorally Isolated Species of Darters (Percidae: Etheostoma)

Abstract: Identifying the manner in which reproductive barriers accumulate during lineage divergence is central to establishing general principles of species formation. One outstanding question is which isolating mechanisms form the first complete barrier to gene flow in a given lineage or under a particular set of conditions. To identify these initial reproductive barriers requires examining lineages in very early stages of divergence, before multiple reproductive barriers have evolved to completion. We quantified the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
103
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(107 citation statements)
references
References 63 publications
3
103
1
Order By: Relevance
“…Sperm concentrations (sperm/mL) and motility were determined microscopically using Cell-VU® counting chambers. Preparations like these, including some of those studied here, are fully capable of fertilizing fresh darter oocytes [33].…”
Section: Sperm Collectionmentioning
confidence: 98%
See 1 more Smart Citation
“…Sperm concentrations (sperm/mL) and motility were determined microscopically using Cell-VU® counting chambers. Preparations like these, including some of those studied here, are fully capable of fertilizing fresh darter oocytes [33].…”
Section: Sperm Collectionmentioning
confidence: 98%
“…In addition, multiple species of darters may co-occur in a given habitat, making reproductive barriers of primary importance in maintaining species boundaries. For example, Mendelson et al [33] demonstrated that sperm of Etheostoma hopkinsi will outcompete those of E. luteovinctum for fertilization of conspecific (same-species) eggs. Such conspecific sperm precedence represents a potentially important barrier to genetic exchange between species (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The relative contribution of isolating barriers may differ; therefore, multiple postzygotic mechanisms across life history stages need to be assessed in order to determine the collective strength of reproductive isolation (Ramsey et al 2003, Mendelson et al 2007. Caribbean acroporids have a complex life cycle which includes external fertilization and a pelagic larval stage.…”
Section: Introductionmentioning
confidence: 99%
“…Heterospecific sperm precedence may result from sexual conflict. Through sexually antagonistic coevolution, females may have evolved strong resistance to conspecific but not to heterospecific sperm, leading to increased fertilization success of heterospecific sperm after interspecific matings (Parker & Partridge, 1998;Martin & Hosken, 2004;Arnqvist & Rowe, 2005;Mendelson, Imhoff & Venditti, 2007). Although the mechanism for the observed sperm precedence in backcrosses with V. contectus females is not yet known, it may be that female-mediated processes are involved.…”
Section: Discussionmentioning
confidence: 97%